Distribution of Dust Exposure and Risk Factor Analysis of Symptoms of Respiratory Disorder Among Brick Industry Workers in Temanggung Regency, Central Java Province - Muhammad Fadli Ramadhansyah; Hanung Nurany; Bayu Kusuma Adi; Supinah; Laliyanto; Ike Rachmawati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The brick industry sector has the capacity to generate pollution in the form of harmful dust particles that can adversely affect the environment and workers health. The research uses a quantitative approach with an analytical observational design, cross sectional study. In addition, researchers conducted an analysis of risk factors related to respondent obiter total dust particulate levels, inhaled dust levels, working duration, exposure duration, and the utilization of personal protective equipment. The measurement results showed the average total dust level was 1748.47 µg/Nm3 and the average respirable dust level of 75 respondents was 4.56 mg/m3. This increases the risk of respiratory symptoms such as coughing, coughing up phlegm, and shortness of breath. Variables associated with respiratory symptoms were inhaled dust levels (p=0.023), working period (p=0.040), exposure duration (p=0.032), and use of personal protective equipment (p=0.015). The multivariate test resulted in four significant variables: inhaled dust level (p=0.022), working period (p=0.039), exposure duration (p=0.029), and use of personal protective equipment (p=0.023). In conclusion, the combination of inhaled dust levels, longer work periods, exposure duration, and inadequate use of PPE increased respiratory symptoms in workers by 99.5%.